(untitled) (Bangladesh Journal of Medical Education, 2025)
Background: Bangladesh is experiencing advancements in postgraduate medical education day by day, but its effectiveness remains under scrutiny. The study achieved views from postgraduate medical course students, recently (within two years of passing) passed postgraduate doctors and postgraduate course teachers. In-depth interviews were recorded from various potentials stakeholders, including professors of medicine and allied disciplines, medical educationists, administrators and policymakers. Methods: The study was a descriptive type of cross-sectional study utilizing both the qualitative and quantitative approaches (mixed method study) for one year from 1 July/2023 to 30 June /2024. Quantitative part was done at different medical university/institutes/colleges (government and nongovernment) having postgraduate courses in Dhaka city and out of Dhaka city. Qualitative data were collected from six postgraduate medical institutes. Results: The study summarized the key findings regarding stakeholders’ views. Majority students wanted to study in clinical subjects especially in Internal Medicine in post-graduation. Highest number of participants were male in post-graduation courses. The study emphasizes the need for significant reforms to enhance the quality and effectiveness of postgraduate medical education in Bangladesh. Key issues highlighted include the need for updated curricula, improved faculty development/teachers training, better infrastructure, logistic support, increased research opportunities, incorporation of modern assessments methods and supervision by local & higher authorities. Conclusion: This study would highlight the importance of addressing stakeholder concerns to create a robust postgraduate medical education system in Bangladesh. BJME, Volume-16, Issue-02, July 2025: 39-66